Pendidikan Kesehatan dan Peningkatan Kesiapan Masyarakat Sebagai Bystender CPR dalam Pemberian Pertolongan Pertama Henti Jantung - Ramli, Rachmat; Pannyiwi, Rahmat; Musdalifah, Musdalifah; Achmad, Viyan Septiyana; Saputra, M. Khalid Fredy; Mesa, Nofita Dewi Kok (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Cardiac Arrest or cardiac arrest is a condition of sudden loss of heart function to pump blood. This causes a lack of oxygen distributed throughout the body, especially to the brain and heart. If the brain lacks oxygen, brain cells will die and result in loss of consciousness. The purpose of the activity is to minimize the occurrence of disability or even death in victims who experience out-of-hospital cardiac arrest (OHCA) and the community is able to provide first aid to save the victim, alleviate the victim's suffering and prevent further harm until better assistance is provided and bring the victim to the nearest medical team to reduce the level of morbidity and mortality. The results of this PkM activity have increased the health status and independence of the community with indicators that the community's ability to practice basic life support procedures for cardiac arrest. The conclusion is that health education is to improve health status, prevent the onset of disease and increase health problems.